The effect of local anesthesia and tooth extraction on blood pressure and heart rate - Al-Yasiry , Anas; Hindy, Ahmad; Al-Jammali, Zainab Mahmood; Almuthaffer, Azad; Ghanim, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The aim: show the effect of adrenaline in local dental anesthesia on the heart rate and blood pressure. Method: The number of the patients twenty seven (13male &14 female) and the age ranged from(25-36) years old. Three readings were taken for both systolic and diastolic blood pressure were measured (in mmHg), and heart rate. At three different times: waiting room before giving the anesthesia, after the patient was taken anesthesia, after the extraction of tooth. Result: there is no significant differences between pre-anesthetic , post -anesthetic and post- extraction for systolic pressure, the mean of systolic pressure increased after giving anesthesia about(122.11), but after extraction it will decrease to about (121.11), there is no significant differences between the pre-anesthetic, post – anesthetic, pre-anesthetic post- extraction for systolic pressure. There is increase in the heart rate mean (85.44) after giving anesthesia, but after extraction it will decline (80.56), and there is significant differences between pre-anesthetic and post- extraction heart rate. Conclusion: The study refer for the safety of adrenaline by measurement of blood pressure and heart rate for control patients but the anxiety and stress of the patients made different in measurement of blood pressure and heart rate also the adrenaline may increase the blood pressure and heart rate if increase dose.